2019
DOI: 10.1073/pnas.1815030116
|View full text |Cite
|
Sign up to set email alerts
|

Ef-cd locus shortens rice maturity duration without yield penalty

Abstract: The contradiction between “high yielding” and “early maturing” hampers further improvement of annual rice yield. Here we report the positional cloning of a major maturity duration regulatory gene,Early flowering-completely dominant(Ef-cd), and demonstrate that natural variation inEf-cdcould be used to overcome the above contradictory. TheEf-cdlocus gives rise to a long noncoding RNA (lncRNA) antisense transcript overlapping theOsSOC1gene.Ef-cdlncRNA expression positively correlates with the expression ofOsSOC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 45 publications
(48 reference statements)
1
61
0
1
Order By: Relevance
“…Other flowering time-related lncRNAs, including FLOWERING LONG INTERGENIC NON CODING RNA ( FLINC ), CDF5 LONG NONCODING RNA ( FLORE ), LDMAR , PHOTOPERIOD-SENSITIVE GENIC MALE STERILITY 1 ( PMS1T ) and Ef-cd , have been recently discovered in Arabidopsis or rice (Ding et al 2012a , b ; Fan et al 2016 ; Henriques et al 2017 ; Severing et al 2018 ; Fang et al 2019 ). FLINC regulates ambient temperature-mediated flowering.…”
Section: Functions and Molecular Mechanisms Of Lncrnas In Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other flowering time-related lncRNAs, including FLOWERING LONG INTERGENIC NON CODING RNA ( FLINC ), CDF5 LONG NONCODING RNA ( FLORE ), LDMAR , PHOTOPERIOD-SENSITIVE GENIC MALE STERILITY 1 ( PMS1T ) and Ef-cd , have been recently discovered in Arabidopsis or rice (Ding et al 2012a , b ; Fan et al 2016 ; Henriques et al 2017 ; Severing et al 2018 ; Fang et al 2019 ). FLINC regulates ambient temperature-mediated flowering.…”
Section: Functions and Molecular Mechanisms Of Lncrnas In Plantsmentioning
confidence: 99%
“…After floral transition, the inflorescence meristem starts to produce floral meristems, which in turn give rise to different types of floral organs. Nowadays, a number of lncRNAs such as LINC-AP2 (Gao et al 2016 ), LONG-DAY SPECIFIC MALE-FERTILITY-ASSOCIATED RNA (LDMAR) (Ding et al 2012a , b ), PHOTOPERIOD-SENSITIVE GENIC MALE STERILITY T ( PMS1T ; Fan et al 2016 ), and EARLY FLOWERING-COMPLETELY DOMINANT ( Ef-cd ; Fang et al 2019 ) have been found to regulate diverse aspects of flower and reproductive development (see Supplemental table S1 for a more comprehensive list of examples). LINC-AP2 is an intergenic lincRNA close to the flower developmental regulatory TF gene APETALA2 ( AP2) .…”
Section: Functions and Molecular Mechanisms Of Lncrnas In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…6442S-7 showed a completely dominant earlymaturing phenotype, and a dominant earliness gene, designated Early flowering-completely dominant (Ef-cd), was roughly mapped to the short arm of rice chromosome 3 (Deng et al, 2001). After 18 years of effort, Ef-cd was finally cloned by map-based cloning (Fang et al, 2019). Interestingly, Ef-cd encodes a long noncoding RNA (lncRNA) that is transcribed from the antisense strand of OsSOC1, which encodes a flowering activator in rice.…”
Section: Cloning Of Ef-cd and Its Action Mechanismmentioning
confidence: 99%
“…Recent studies have demonstrated that lncRNAs participate in diversified biological functions in different organisms [23,24]. Nevertheless, only a few lncRNAs have been well characterized in plants, including COOLAIR and COLDAIR in the regulation of flowering in Arabidopsis [25,26], INDUCED BY PHOSPHATE STARVATION1, which is involved in phosphate uptake [27,28]; Enod40, which is involved in nodulation [29,30]; LDMAR, which is required for pollen development in rice [31]; LAIR, which increases rice grain yield [32]; and Ef-cd, which shortens rice maturity duration without a yield penalty [33]. Remarkably, accumulated evidence has demonstrated the involvement of lncRNAs in biotic and abiotic stress responses in plants [34].…”
Section: Introductionmentioning
confidence: 99%